Can people trust what they don't understand? Role of language and trust for financial inclusion - Aleksandra Nagańska; Stanisław Cichocki (Central European Economic Journal (CEEJ), 2022)
The aim of this paper is to look at determinants of financial inclusion through the lens of comprehension of financial concepts and financial language. Specifically, we are interested in which factors are important should this comprehension be absent. We show that, in the context of finance, communication is an important transmission channel through which individuals are encouraged or discouraged to participate in the financial system. We argue that the unfamiliarity with products and the complexity of language used in the banking sector tend to limit trust granted to financial institutions. We test the hypothesis that linguistic diversity is a strong instrument for the impact of the lack of communication on trust. Applying Ordinary Least Squares and probit regression, quantile regression, and instrumental variables to cross country and individual-level data, we show the importance of individual and cultural characteristics and demonstrate the role of trust and communication for financial inclusion. The outcome is consistent for different model specifications.
Keywords: O12; G29; 330; Financial inclusion; financial literacy; trust; linguistic diversity